Ropivacaine Versus Bupivacaine for Penile Block in Pediatric Circumcision: A Quasi-Randomized Clinical Trial - Rana Mohammad Yousef; Aqeel Jawad Abdulsahib; Razieh Ramezani; Afzal Shamsi; Elham Shahidi Delshad (Archives of Anesthesia and Critical Care, 2026)
Background: Circumcision is one of the most frequently performed pediatric surgeries. Effective perioperative analgesia is essential to minimize pain, reduce stress responses, and facilitate early recovery. This study aimed to compare the analgesic efficacy, hemodynamic effects, and recovery outcomes of ropivacaine versus bupivacaine in penile nerve block among children undergoing circumcision. Methods: In this quasi-randomized clinical trial conducted at Bahrami Children’s Hospital (Tehran, Iran) from November 2024 to January 2025, 66 male children aged 3 months to 3 years (ASA I–II) scheduled for elective circumcision were consecutively enrolled. Based on sequential allocation, participants received either 0.2% ropivacaine (Group R) or 0.25% bupivacaine (Group B) at 0.2 mL/kg for dorsal penile block. Hemodynamic parameters were recorded at key perioperative time points. Pain was assessed using the FLACC scale, and recovery time and fentanyl consumption were documented. Results: Group R demonstrated significantly lower heart rates and higher systolic blood pressure at post-induction, post-incision, and end-of-surgery time points (p < 0.05). The need for intraoperative fentanyl was lower in group B (24.2% vs. 66.7%, p < 0.001), while postoperative FLACC scores were lower in Group R (p = 0.024). Recovery time was significantly shorter in the ropivacaine group (p < 0.001). No adverse events occurred. Conclusion: Both drugs (ropivacaine and bupivacaine) were safe and effective. Ropivacaine provided better analgesia and faster postoperative recovery, while bupivacaine reduced intraoperative opioid use. These findings suggest that drugs should be selected based on individual clinical preferences.